2015
DOI: 10.1128/aem.03268-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering Activates Biosynthesis of Aromatic Fumaric Acid Amides in the Human Pathogen Aspergillus fumigatus

Abstract: The Aspergillus fumigatus nonribosomal peptide synthetase FtpA is among the few of this species whose natural product has remained unknown. Both FtpA adenylation domains were characterized in vitro. Fumaric acid was identified as preferred substrate of the first and both L-tyrosine and L-phenylalanine as preferred substrates of the second adenylation domain. Genetically engineered A. fumigatus strains expressed either ftpA or the regulator gene ftpR, encoded in the same cluster of genes, under the control of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…[6] Isolation of genomic A. fumigatus DNA and Southern blot analysis were as previously described. Fumaryl-l-tyrosine and fumaryl-l-phenylalanine were synthesized as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[6] Isolation of genomic A. fumigatus DNA and Southern blot analysis were as previously described. Fumaryl-l-tyrosine and fumaryl-l-phenylalanine were synthesized as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Fumaryl-l-tyrosine and fumaryl-l-phenylalanine were synthesized as described previously. [6] Isolation of genomic A. fumigatus DNA and Southern blot analysis were as previously described. [14] Synthetic DNA was produced by Life Technologies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of homologous NRPS biosynthetic genes of which one is silent has been found earlier in work on Aspergillus fumigatus (Steinchen et al ., ). Genetic engineering and metabolite analysis revealed that both NRPSs are functional and produce a similar set of small metabolites (Kalb et al ., ). Apparently, the effort of harbouring redundant NRPS pathways is prevalent in filamentous fungi and might emphasize the significance of the corresponding SMs.…”
Section: Resultsmentioning
confidence: 97%